The ESPREssO Action Database: Collecting and assessing measures for disaster risk reduction and climate change adaptation. (September 2020) - Baills, Audrey; Grandjean, Gilles; Maspataud, Aurélie; Ettinger, Susanne; Abad, Jaime; Dias, Nuwan; Albris, Kristoffer; Hemmers, Jaqueline; Clegg, Georgina; Martucci, Casimiro
Abstract: The Action Database (ADB) was developed during the ESPREssO project (Enhancing Synergies for Disaster Prevention in the European Union) in order to store and analyze relevant ideas emerging during the project to deal with the challenges. It provides the opportunity to formalize discussions and to store their content in a synthetic format, as well as to collect experiences and evaluate the impacts they had at their respective scales of implementation and on different parameters. The major aim of the ESPREssO-ADB tool, and its main innovation, is to deal with multi-hazard and multi-challenge actions, in an international context and notably in a cross-border initiative. The ESPREssO project aimed at contributing to a new strategic vision on Disaster Risk Reduction (DRR) and Climate Change Adaptation (CCA) in Europe. To do so, stakeholders working with CCA and/or DRR in Europe were consulted to identify measures boosting adaptation or societies' resilience. Each idea, measure or comment was stored and ranked in the ADB using qualitative criteria based on the Sendai Priorities and the SHIELD model proposed by the ESPREssO Team. Each action was assessed through multi-criteria analysis and effectiveness was approached under two different angles. The first one in line with the priorities of the Sendai Framework; and the second one with the SHIELD model. This model incorporate recommendations on how to optimize risk management capabilities through DRR. Positive actions had fed the Vision Paper and Guidelines produced by the project. This paper describes in details the ADB structure and the multi-criteria analysis performed.